Resiliensi Anak Usia 4-6 Tahun (Studi Kasus Pada Keluarga Broken Home) - Alham, Saskia; Sabani, Fatmarida; Hasis, Pertiwi Kamariah; Yusuf, Munir; Eka Poppi Hutami (Jurnal Pendidikan Anak Usia Dini Indonesia, 2024)
This research aims to determine the effect of Broken Home on children's resilience, the reasons for the emergence of resilience in children aged 4-6 years, and the variables that influence the resilience of children who grow up in Broken Home conditions. The researcher used qualitative research methods to conduct this investigation. Structured interviews, observation sheets, and documentation were used as data collection methods. The triangulation method is used in the data analysis approach, namely: (1) theoretical triangulation, namely comparing data with previous hypotheses (2) triangulation of actual data sources, namely testing the truth using historical data sources from interviews. documentation and observation (3) methodological triangulation using surveys and interviews to collect data on certain topics. The results of the research show that the resilience that occurs in the five children aged 4-6 years can be seen through the six different aspects of children's resilience abilities, namely (1) emotional regulation, (2) impulse control, (3) optimism, (4) empathy , (5) reaching out, and (6) self-efficacy.